High-Density Lipoprotein-Mediated Cholesterol Efflux Capacity Is Improved by Treatment With Antiretroviral Therapy in Acute Human Immunodeficiency Virus Infection. (16th December 2014) - Lo, Janet; Rosenberg, Eric S.; Fitzgerald, Michael L.; Bazner, Suzane B.; Ihenachor, Ezinne J.; Hawxhurst, Victoria; Borkowska, Alison H.; Wei, Jeffrey; Zimmerman, Chloe O.; Burdo, Tricia H.; Williams, Kenneth C.; Freeman, Mason W.; et al.
Abstract: Background. Individuals infected with human immunodeficiency virus (HIV) have decreased high-density lipoprotein (HDL)-cholesterol and increased cardiovascular disease (CVD). Reverse cholesterol transport from macrophages may be inhibited by HIV and contribute to increased CVD. Human studies have not investigated longitudinal effects of HIV and antiretroviral therapy (ART) on cholesterol efflux. Methods. Subjects with acute HIV infection were randomized to ART or not. Cholesterol efflux capacity was determined ex vivo after exposure of murine macrophages to apolipoprotein B-depleted patient sera obtained at baseline and after 12 weeks. Results. After 12 weeks, HIV RNA decreased most in subjects randomized to ART. Available data on cholesterol demonstrated that efflux capacity from Abca1 +/+ macrophages was increased most by sera obtained from ART-treated subjects (20.5% ± 5.0% to 24.3 % ± 6.9%, baseline to 12 weeks, P = .007; ART group [ n = 6] vs 18.0 % ± 3.9% to 19.1 % ± 2.9%, baseline to 12 weeks, P = .30; untreated group [ n = 6] [ P = .04 ART vs untreated group]). Change in HIV RNA was negatively associated with change in Abca1 +/+ macrophage cholesterol efflux ( r = − 0.62, P = .03), and this finding remained significant ( P = .03) after controlling for changes in HDL-cholesterol, CD4 + cells, and markers of monocyte or macrophage activation. Conclusions. In subjects acutely infected with HIV, ATP-binding cassette transporter A1-mediated cholesterol efflux was stimulated to a greater degree over time by apolipoprotein B-depleted serum from subjects randomized to ART. The improvement in cholesterol efflux capacity is independently related to reduction in viral load.